1889 Ariz. Terr. Laws 30 §1 - (:unkn) unknown (General Publisher, 1889)
Prohibited the carry on the person, or in saddlebags, of any pistol, dirk, dagger, slung-shot, sword-cane, spear, brass knuckles, Bowie-knife, or any other kind of knife manufactured for purposes of offense or defense. Only applied within any settlement, town, village or city. Violators fined not less than twenty-five nor more than one hundred dollars, and shall forfeit the weapons to the county upon conviction.
--
Keywords: CARRY